Comparison of Peel Pouch Leakage between Continuous Sealing Machine and Hand Sealing Machine - Luengpailin, Somkiat; Klangthong, Angkana; Kongsomboon, Supaporn; Mueangwaeng, Suphaphit; Pitanupong, Jeerapa; Thongnak, Poorichaya; Tanpleerat, Supreeya (Khon Kaen University Dental Journal, 2020)
The purpose of this study was to compare the leakage on the peel pouch packages sealed by heat or a continuous sealing machine and a hand sealing machine. The samples included 600 packages sealed with the hand sealing machine and 500 packages sealed with the continuous sealing machine. All the samples contained one glass ball and were sealed 1 inch away from the edge. Then, the samples were sterilized at 121 degrees Celsius with 1.5 bar of pressure for 20 minutes. The samples were tested for leakage by using 0.05% blue toludine which was sprayed along the seal line and 5 millimeters up from the seal. The color was let to coat with the package for at least 5 seconds but no more than 20 minutes. Then, the package was turned so that the color covered the entire seal line. A waterproof pen was used to mark any leakage. When the color dried, the plastic sheet was removed and the color would stick on the leaking holes which were later marked by the pen. The results were read and analyzed with statistics including Chi – square test at 95% confidence level. The results showed that the proportion of leakage on the packages sealed with the continuous sealing machine and the hand sealing machine was statistically significant (P = 0.002), and the difference of leakage ratio was at 1.83 percent (95% CI = 0.76% - 2.91%). In conclusion, the leakage ratio of the peel pouch packages sealed by continuous sealing machine is lower than hand sealing machine.